PJMHS 2021
DOI: 10.53350/pjmhs2115123970
|View full text |Cite
|
Sign up to set email alerts
|

Study the effect of Bilateral Nasal Packing on Systemic Blood Pressure and Prevalence of Complications Associated with Nasal Packing in Patients who had Undergone Septoplasty

Abstract: Aim: The main objective of this study was to determine the effect of bilateral nasal packing on systemic blood pressure in patients treated with septoplasty surgical procedure. Study Design: Retrospective study. Place and Duration: This study was conducted at the department of ENT/ Head & Neck Surgery, Lady Reading Hospital MTI, Peshawar and Chaudhary Muhammad Akram Teaching and Research Hospital, Lahore for duration of one year from October 2020 to September 2021. Methods: One hundred and two men and wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Naseem et al demonstrated an increase in mean systolic and diastolic arterial blood pressures before and after surgery, respectively. 13 Banglawala et al in a meta-analysis of 2 randomized controlled trials and 12 prospective observational researches, only 9 demonstrated statistically significant variation in at least 1 of the cardio-respiratory parameters studied, the aggregate results being inconsistent with no major cardio-respiratory event. 14 Ribbon gauze impregnated with Vaseline® nasal packs are plagued with significant ingress of mucosal tissue inside its webbed outline often causing bleeding upon removal.…”
Section: Discussionmentioning
confidence: 97%
“…Naseem et al demonstrated an increase in mean systolic and diastolic arterial blood pressures before and after surgery, respectively. 13 Banglawala et al in a meta-analysis of 2 randomized controlled trials and 12 prospective observational researches, only 9 demonstrated statistically significant variation in at least 1 of the cardio-respiratory parameters studied, the aggregate results being inconsistent with no major cardio-respiratory event. 14 Ribbon gauze impregnated with Vaseline® nasal packs are plagued with significant ingress of mucosal tissue inside its webbed outline often causing bleeding upon removal.…”
Section: Discussionmentioning
confidence: 97%
“…The practice also reduces the possibility of complications such as adhesions and septal hematoma. Although nasal packing stabilizes the septum and thus reduces the risk of post-operative deviation [8], this practice can also cause hypoxemia and hypercapnia [9]. Furthermore, since nasal packing causes nasal obstruction, the resulting obligatory mouth breathing may have systemic effects such as insomnia, breathing difficulty, decreased oxygen levels in the blood, and toxic shock syndrome [10].…”
Section: Introductionmentioning
confidence: 99%